Eletrical safety [electronic resource]. (Virginia ITC Learning Corporation, 1996)
Summary: Designed to help student develop an understanding of electrical personal protective equipment required by OSHA. Describes hand and arm protection, eye, face and head protection, general protective equipment, and additional practices that will i
Keywords: Electric engineering -- Safety measures